Startupland : how three guys risked everything to turn an idea into a global business - Svane, Mikkel (Jossey-Bass, A Wiley Brand, 2014)
"Startupland is the story of Zendesk, founded in the kitchen of a Copenhagen loft, and now a 500-person company with customers in 140 countries and one of the hottest companies in Silicon Valley. Zendesk provides customer service software to major clients. Much like Zendesk's mission itself--to remove the friction, the barriers and the mystery in order to make software easier and more approachable--this book removes some of the myths about startups and startup founders. Instead of making things murky and complicated, this book inspires and empowers you to follow your own dream and create your own story. This book makes you want to go out and do something--not just because there's an opportunity in the market, or a path to make money, but because you want to build something that you believe in, are determined to design your own destiny, and understand that what you do matters. While there are books by consultants who tell you how to build businesses, or entrepreneurs now running billion dollar businesses, there are few books from people still in the trenches who acutely remember what it was like. Startupland is indispensable reading for all entrepreneurs who want to make their ideas the next big thing"--